40.1k views
1 vote
Find all the values of:

a. (-i)^i

b. (-1)^i

please help we with this complex variable problem.

User Rok Benko
by
6.1k points

1 Answer

1 vote

Answer:

(a)
(-i)^(i)=e^(i \log (-i))=e^(i (\log \lvert -i \rvert +i(\arg (-i)+2\pi n)))=e^{i(0+i(-(\pi )/(2)+2\pi n))}=e^{-(-(\pi)/(2)+2\pi n)}=e^{(\pi)/(2)-2\pi n, where
n\in \mathbb{Z}

(b)
(-1)^(i)=e^(i \log (-1))=e^(i (\log 1 +i(\pi+2\pi n)))=e^(-(\pi+2\pi n)), where
n\in \mathbb{Z}.

Explanation:

Let's remember the definition of complex exponents. If
z is a nonzero complex number and
c is a complex number, we define
z^(c) by


z^(c)=e^(c \log z)

Where the
\log function is the complex logarithm function. That is to say,
\log z=\log \lvert z\rvert + i(\arg z+2\pi n), where
n\in \mathbb{Z}. With this in mind we can calculate the given powers as follows:

(a)
(-i)^(i)=e^(i \log (-i))=e^(i (\log \lvert -i \rvert +i(\arg (-i)+2\pi n)))=e^{i(0+i(-(\pi )/(2)+2\pi n))}=e^{-(-(\pi)/(2)+2\pi n)}=e^{(\pi)/(2)-2\pi n, where
n\in \mathbb{Z}

(b)
(-1)^(i)=e^(i \log (-1))=e^(i (\log 1 +i(\pi+2\pi n)))=e^(i(0+i(\pi +2\pi n)))=e^(-(\pi+2\pi n)), where
n\in \mathbb{Z}.

This are all the values of the given powers.

User Uwe Plonus
by
5.6k points